PENGARUH LINGKUNGAN KERJA, STRESS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BUMI SENTOSA DENPASAR - Gde Bayu Surya Parwita; Made Ika Prastyadewi; Putu Yuni Sintia Dewi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
This research aims to determine the influence of the work environment, work stress, work discipline and employee performance. This research was conducted at PT. Bumi Sentosa Denpasar using a sample of 45 employees. The sampling technique used was the census method. Data collection was carried out through observation, interviews and questionnaires. The data analysis technique used is multiple linear regression analysis which is processed using SPSS version 26 software. Based on the results of the analysis, this research shows that the work environment has a positive and significant effect on employee performance at PT. Bumi Sentosa Denpasar. This means that the better the work environment, the better the employee performance at PT. Bumi Sentosa Denpasar. Work stress has a positive and significant effect on employee performance at PT. Bumi Sentosa Denpasar. This means that the better the work stress, the better the employee performance at PT. Bumi Sentosa Denpasar. Work discipline has a positive and significant effect on employee performance at PT. Bumi Sentosa Denpasar. This means that the better the work discipline, the better the employee performance at PT. Bumi Sentosa Denpasar.